2023
DOI: 10.21203/rs.3.rs-3272441/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional Imaging Derived ADHD Biotypes Based on Deep Clustering May Guide Personalized Medication Therapy

Jing Sui,
Aichen Feng,
Yuan Feng
et al.

Abstract: Attention deficit hyperactivity disorder (ADHD) is one prevalent neurodevelopmental disorder with childhood onset, however, there is no clear correspondence established between clinical ADHD subtypes and primary medications. Identifying objective and reliable neuroimaging markers for categorizing ADHD biotypes may lead to more individualized, biotype-guided treatment. Here we proposed graph convolutional network plus deep clustering for ADHD biotype detection using functional network connectivity (FNC), result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Additionally, a study on inhibitory control established cognitive and neurobiological profiles related to reading abilities, demonstrating significant reading ability variations among groups with different default mode network connectivity patterns (Fekson et al, 2023). Moreover, research on ADHD (Sui et al, 2023) identified two distinct ADHD biotypes with implications for personalized medication therapy, emphasizing the potential of neuroimaging markers in tailored treatment approaches (Yan et al, 2023). Together, these studies highlight the ABCD dataset’s potential role in revealing neurodevelopmental profiles that may contribute to a deeper understanding of mental health, cognitive abilities, and the potential for personalized treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a study on inhibitory control established cognitive and neurobiological profiles related to reading abilities, demonstrating significant reading ability variations among groups with different default mode network connectivity patterns (Fekson et al, 2023). Moreover, research on ADHD (Sui et al, 2023) identified two distinct ADHD biotypes with implications for personalized medication therapy, emphasizing the potential of neuroimaging markers in tailored treatment approaches (Yan et al, 2023). Together, these studies highlight the ABCD dataset’s potential role in revealing neurodevelopmental profiles that may contribute to a deeper understanding of mental health, cognitive abilities, and the potential for personalized treatment strategies.…”
Section: Introductionmentioning
confidence: 99%